Partial characterization and in vitro evaluation of a lytic bacteriophage for biocontrol of Campylobacter jejuni in mutton and chicken meat - Tze, Young Thung; Lee, Epeng; Mahyudin, Nor Ainy; Wan Mohamed Radzi, Che Wan Jasimah; Mazlan, Nurzafirah; Tan, Chia Wanq; Radu, Son (Wiley, 2020)
Campylobacter jejuni is a major foodborne pathogen causing acute bacterial enteritis worldwide. Screening of novel bacteriophages as biocontrol tools to eliminate C. jejuni in food during pre- and postharvest is an emerging research field. In this study, we partially characterized C. jejuni bacteriophage CJ01 for potential use as biocontrol agent. Transmission electron microscopy revealed bacteriophage CJ01 belonged to the Myoviridae family with a genome size of approximately 136 kb. The results of host range assay revealed CJ01 was able to infect C. jejuni and C. lari strains, with burst size about 35 phages per infected cell and latent period of 30 min. The effectiveness of bacteriophage CJ01 (with 100 multiplicity of infection = 100) was determined in mutton and chicken meat artificially contaminated with C. jejuni. The amount of C. jejuni in treated mutton and chicken meat were significantly reduced by 1.70 log CFU/g and 1.68 log CFU/g, respectively, after 48 hr stored at refrigeration temperature (4°C). The data presented here suggest that bacteriophage CJ01 can be used as a postharvest biocontrol agent.